The U.S. Army War College military education in a democracy - Stiehm, Judith Hicks (Temple University Press, 2002)
We are all familiar with ROTC, West Point, and other institutions that train young men and women to be military officers. But few people know of the U.S. Army War College, where the Army's elite career officers go for advanced training in strategy, national security policy, and military-government policymaking. This book takes readers inside the U.S. Army War College to learn about the faculty, staff, administration, andcurriculum.Established in 1901, the school's mission has evolved from teaching the skills of war to training officers to negotiate both the complex world of modern strategy and the civilian bureaucracy in Washington. More like a professional graduate program than an academic graduate school, much of the education takes the form of exercises and simulations.Judith Stiehm, who holds the U.S. Army Distinguished Civilian Service Medal, allows readers to judge whether the U.S. Army War College successfully prepares its students for their many roles. She is skeptical that instructors can fulfill this difficult task in an era where civilians expect our military to be invincible, to win without casualties, and to serve as peacekeepers.The Military answers to the people of the United States and it is our responsibility to know how it operates at all levels. This book is a good place to start. Author note: Judith Hicks Stiehm is Professor of Political Science at Florida International University and the author of Arms and the Enlisted Woman; It's Our Military, Too (both published by Temple); and a report on women in peacekeeping for the Lessons Learned Unit of the United Nations' (UN) Department of Peacekeeping Operations. A member of the Council on Foreign Relations, she holds the U.S. Army Distinguished Civilian Service Medal.